SAT0532 Efficacy and Safety of Canakinumab in Patients with Active Recurrent or Chronic TNF-Receptor Associated Periodic Syndrome (TRAPS). (9th June 2015) - Lachmann, H.; Cattalini, M.; Obici, L.; Barcellona, R.; Speziale, A.; Joubert, Y.; Junge, G.; Gattorno, M.
Abstract : Background: Tumor necrosis factor receptor-1 associated periodic syndrome (TRAPS) is a periodic fever syndrome, whose main symptoms are rashes, musculoskeletal and abdominal pain, and periorbital edema. Although TNF inhibitors have been shown to be effective in some patients, their efficacy tends to decrease over time. 1-4 Anti-IL-1 treatments have also been used in an effort to provide long term control of the inflammatory manifestations. Objectives: The proof of concept study was designed to assess safety, efficacy, and pharmacokinetics (PK) /pharmacodynamic (PD) data upon canakinumab (CAN) and to determine the appropriate dosing for further development of CAN treatment in patients with TRAPS. Methods: This was an open-label, single treatment arm, efficacy and safety study of monthly CAN 150 mg (2 mg/kg for patient ≤40 kg) SC in patients with active recurrent or chronic TRAPS. Patients were treated for 4-months with a maximum 5-month follow-up period. The initial follow-up period was followed by a maximum 24-month long-term treatment period. The primary efficacy outcome was induction of complete or almost complete response in active TRAPS patients at Day 15 after first CAN dosing. Results: A total of 20 patients were exposed to study medication, out of which 18 (90%) patients completed the study. Primary endpoint showed that 18 patients [90%; 95% CI: 75.1, 99.9] achieved a complete or almost complete response at Day 15, while 20 (100%) and 12 (60%) patients had clinical and serological remission, respectively (Table ). Already at Day 8, 16 patients (80%) achieved a complete or almost complete response, while 18 (90%) and 7 (35%) patients had clinical and serological remission, respectively. A total of 60% of patients experienced study drug-related AEs, most commonly upper respiratory tract infections. Seven patients (35%) experienced SAEs, none of which were related to study drug. Furthermore, there were no deaths during the study. Conclusions: Canakinumab was effective in rapidly alleviating clinical signs and symptoms of TRAPS, whilst normalizing serological inflammatory markers and providing sustained disease control. The safety profile was consistent with previous canakinumab studies in other indications. These data support the ongoing development of canakinumab in this therapeutic area. References: Simon A, et al. Am.J.Med 2004;117:208-10. Weyhreter H, et al. J Pediatr 2003;142:191-3. Jacobelli S, et al. Rheumatology (Oxford) 2007;46(7):1211-2. Arostegui JI, et al. Eur.J.Pediatr 2005;164:13-6. Disclosure of Interest: H. Lachmann Grant/research support from: Novartis, Consultant for: Novartis, M. Cattalini Consultant for: Novartis, SOBI, Speakers bureau: Novartis, L. Obici Consultant for: Novartis, Speakers bureau: Novartis, R. Barcellona: None declared, A. Speziale Employee of: Novartis, Y. Joubert Employee of: Novartis, G. Junge Employee of: Novartis, M. Gattorno Grant/research support from: Novartis, SOBI, Speakers bureau: Novartis, SOBI